Frequent carbohydrate ingestion reduces muscle glycogen depletion and postpones fatigue relative to a single bolus - Menzies, C.; Wood, M.; Thomas, J.; Hengist, A.; Walhin, J.-P.; Jones, R.; Tsintzas, K.; Gonzalez, J. T.; Betts, J. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
The timing of carbohydrate ingestion and how this influences net muscle glycogen utilization and fatigue has only been investigated in prolonged cycling. Past findings may not translate to running because each exercise mode is distinct both in the metabolic response to carbohydrate ingestion and in the practicalities of carbohydrate ingestion. To this end, a randomized, cross-over design was employed to contrast ingestion of the same sucrose dose either at frequent intervals (15 × 5 g every 5 min) or at a late bolus (1 × 75 g after 75 min) during prolonged treadmill running to exhaustion in six well-trained runners (VO2max 61 ± 4 ml·kg-1·min-1). The muscle glycogen utilization rate was lower in every participant over the first 75 min of running (Delta 0.51 mmol·kg dm-1·min-1; 95% confidence interval [-0.02, 1.04] mmol·kg dm-1·min-1) and, subsequently, all were able to run for longer when carbohydrate had been ingested frequently from the start of exercise compared with when carbohydrate was ingested as a single bolus toward the end of exercise (105.6 ± 3.0 vs. 96.4 ± 5.0 min, respectively; Delta 9.3 min, 95% confidence interval [2.8, 15.8] min). A moderate positive correlation was apparent between the magnitude of glycogen sparing over the first 75 min and the improvement in running capacity (r = .58), with no significant difference in muscle glycogen concentrations at the point of exhaustion. This study indicates that failure to ingest carbohydrates from the outset of prolonged running increases reliance on limited endogenous muscle glycogen stores—the ergolytic effects of which cannot be rectified by subsequent carbohydrate ingestion late in exercise.